Peran Kompetensi Staf Akuntansi Dalam Pencapaian Kualitas Informasi Keuangan Daerah Pada Sekolah Tinggi Ilmu Tarbiyah (STIT) Batu Bara - Khairani Kamilah Muhammad; Nurlaila Harahap (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to understand the level of competency of accounting staff at the Tarbiyah College of Science (STIT) Batu Bara, the quality of regional financial information, the role of accounting staff competency at the Tarbiyah College of Science (STIT) Batu Bara, and its impact on the competency of accounting staff. The research method used is Census with a qualitative and quantitative approach. The analysis tool used is simple regression. The research results show that the important role of accounting staff competencies such as a thorough understanding of financial accounting standards, proficiency in financial analysis, and technical proficiency in accounting information systems in maintaining the quality of regional financial data. This shows that there is a need to increase investment in developing the skills of accounting staff through training and continuous education to support the efficiency and effectiveness of financial management in the educational environment. It can be believed that this research can expand knowledge about the relationship between the quality of regional financial information and the ability of accounting staff, especially at the Tarbiyah College of Science (STIT) Batu Bara.